Unveiling the transpassive film failure of 3D printing transition alloys. (1st August 2022) - Guo, Pengfei; Lin, Xin; Macdonald, Digby D.; Ter-Ovanessian, Benoît; Liu, Jianrui; Song, Guangling; Zhang, Yufeng; Ren, Yongming; Lan, Hongbo; Huang, Weidong
Abstract: The failure of transpassive films on transition metal alloys was investigated. The results show that the failure of the transpassive film on 3D printing nickel-based superalloy in flowing NaNO3 solution is dominated by self-induced cracking of the film on niobium-segregated phases and the erosion-induced degradation on the film assisted by cation vacancy condensation at the metal/barrier layer interface. Secondary passivation induces the formation of a transpassive film, the nature of which has been debated for decades. The findings are consistent with a bi-layer structure comprising a point-defective barrier layer that grows into the substrate alloy and a precipitated outer layer. Graphical Abstract: ga1 Highlights: Failure mechanism of the transpassive film was investigated for the first time. The exist of the cation vacancies in the transpassive film was confirmed. Secondary passivation induces the formation of the transpassive film.